Utilização de caulim como um potencial adsorvente de baixo custo na remoção de poluente orgânico em soluções aquosas - Caponi, Natiela (2017)
Dye industries have great difficulty in effectively treating of wastewater generated, particularly in relation to dyes removal of the effluents, that even in small quantities, gives intense color, contributing to contamination of the environment if inappropriately disposed. Due to these environmental implications, adsorption technique is widely used to remove many types of effluent, because is a potentially versatile and inexpensive alternative. The aim of this work is to analyze the efficiency of natural kaolin as an adsorbent in the removal of organic dyes in aqueous solution. In this study, aqueous solutions of Malachite Green and Crystal Violet dyes were used a contaminant models. Kaolin was characterized by various techniques, which were demonstrated their physicochemical properties. The maximum adsorption capacity of Malachite Green dye was 128 mg g-1, demonstrating the efficient removal capacity using natural kaolin. For crystal violet, an experimental design was used for the obtaining the optimal conditions of adsorption process, resulting in a satisfactory adsorption capacity of 48.8 mg g-1. Therefore, natural kaolin proved to be an adsorbent potential for removing the both dyes in aqueous solutions.